2016
DOI: 10.1002/marc.201600528
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus‐Responsive Nanoparticles and Associated (Reversible) Polymorphism via Polymerization Induced Self‐assembly (PISA)

Abstract: "smart" materials rely on very distinct material responses on a macroscopic and/or microscopic level. This can be achieved by crafting stimulus-responsive polymers into nanostructured materials, including smart nanoparticles, which are receiving increasing attention specifically in the biomedical field. [2,3] Amphiphilic block copolymers are well-known to undergo self-directed assembly in selective solvents providing access to a range of soft matter nanoparticles [4][5][6][7] with applications in coatings, [8]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
137
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(144 citation statements)
references
References 111 publications
(235 reference statements)
1
137
1
5
Order By: Relevance
“…However, variable‐temperature 1 H NMR spectra revealed no obvious change in hydration degree of the core‐forming PDAAM block, suggesting that PDAAM is indeed water‐insoluble even after being attached to a hydrophilic PDMA block. The temperature‐induced morphological transition for this non‐thermoresponsive PDMA‐PDAAM BCP was explained by interfacial plasticization phenomenon . Further studies on cross‐linked lamellae revealed that the kinetics of morphological transition as well as the rheology properties of the dispersions could be adjusted by changing the cross‐linking density.…”
Section: Raft Aqueous Dispersion Pisamentioning
confidence: 89%
See 1 more Smart Citation
“…However, variable‐temperature 1 H NMR spectra revealed no obvious change in hydration degree of the core‐forming PDAAM block, suggesting that PDAAM is indeed water‐insoluble even after being attached to a hydrophilic PDMA block. The temperature‐induced morphological transition for this non‐thermoresponsive PDMA‐PDAAM BCP was explained by interfacial plasticization phenomenon . Further studies on cross‐linked lamellae revealed that the kinetics of morphological transition as well as the rheology properties of the dispersions could be adjusted by changing the cross‐linking density.…”
Section: Raft Aqueous Dispersion Pisamentioning
confidence: 89%
“…Although PHPMA is insoluble in water, it becomes thermally responsive when being attached to a hydrophilic block . PGMA–PHPMA nano‐objects were reported to exhibit a thermally reversible worm‐to‐sphere transition upon cooling from ambient temperature (20–25 °C) to 4 °C .…”
Section: Raft Aqueous Dispersion Pisamentioning
confidence: 99%
“…The recent development of polymerization‐induced self‐assembly (PISA) offers new perspectives in the design of latex particles by surfactant‐free emulsion or dispersion processes, up to a high solids content. The simultaneous self‐assembly and particle growth enables the synthesis of well‐defined core–shell spherical or anisotropic particles formed by self‐assembled block copolymer chains . Moreover, the absence of molecular surfactant circumvents some detrimental effects of molecular surfactant like transparency loss.…”
Section: Methodsmentioning
confidence: 99%
“…As documented in the literature, the thermal activation method could be extended to most of the studied macro‐RATF agents/monomer combinations when the raw materials and formed vesicles are thermally stable . However, in some cases, the high reaction temperature (or later quenching reaction by cooling down) may significantly result in morphology changes for the formed vesicles . From the perspective of downstream construction or application of PISA to artificial bioinspired protocells, thermally powered PISA presents substantial challenges.…”
Section: Pisa An Ex Novo Strategy For Vesicle Formation Growth Andmentioning
confidence: 99%